"Não deixe para amanhã o que você pode fazer hoje": um estudo sobre pré-crastinação em estudantes universitários - Pereira, Andrêsa Fernanda Gomes (2023)
This dissertation aimed to know to what extent personality traits, anxiety and human values explain the phenomenon of pre-crastination. For this, three studies were developed, being structured here in three articles. Article 1, of a theoretical nature, aimed to bring together concepts, definitions and main characteristics, as well as the convergences and divergences with procrastination. In article 2, the elaboration of the Pre-crastination Scale (PE) was proposed, gathering evidence of its validity and psychometric adequacy. In view of this, two studies were carried out, with samples of higher education students, in Study 1, 200 students with a mean age of (Mage = 23,80; SD = 7,9) participated who answered the initial version of the EP, consisting of 25 items and sociodemographic questions. An exploratory factor analysis a threedimensional structure consisting of 18 items that showed satisfactory internal consistency (ω = 0.85). In study 2, we sought to confirm the structure found in the previous study, thus, 200 students with the average age (Mage = 24,42; SD = 7,67) participated, who answered the EP version with 18 items. Through a confirmatory factor analysis, it was possible to prove the three-dimensional structure: Task anticipation (ω = 0.89) Task management (ω = 0.75) and Feelings towards the task (ω = 0.66) [χ² = 232.658; p< 0.001; χ²/gl = 1.76; CFI = 0.92; RMSEA = 0.06 and TLI = 0.91, showing evidence of PE factorability and adequacy. Continuing on, in Article 3, which aimed to explain pre-crastination based on personality traits, anxiety and human values, in a specific way, we sought (1) to know the relationship between precrastination, personality traits, anxiety and values and (2) understand the role of personality traits, anxiety and human values, in explaining the phenomenon of pre-crastination. For this purpose, 400 higher education students with an average age of (Mage = 23,18; SD= 5,1) were interviewed. The participants answered sociodemographic questions and the following instruments: Pre-crastination Scale (EP), Dark Triad Dirty Dozen (DTDD), Questionnaire of Basic Values (QVB) and Cognitive Anxiety Scale. The results showed that pre-crastination was correlated with dark and bright personality traits, anxiety and values of existence, achievement, normative, suprapersonal and interactive, making it possible to confirm the hypotheses outlined. In view of the above, it is estimated that the proposed objectives were achieved, with the construction of a measure that gathered psychometric evidence of factor validity and consistency, in addition to contributing to the dissemination and understanding of such a relevant behavioral trend, starting not only from its origins, but also relates to other constructs.